2020
DOI: 10.1126/scirobotics.aba6251
|View full text |Cite
|
Sign up to set email alerts
|

Field performance of sterile male mosquitoes released from an uncrewed aerial vehicle

Abstract: Genetic control methods of mosquito vectors of malaria, dengue, yellow fever, and Zika are becoming increasingly popular due to the limitations of other techniques such as the use of insecticides. The sterile insect technique is an effective genetic control method to manage insect populations. However, it is crucial to release sterile mosquitoes by air to ensure homogeneous coverage, especially in large areas. Here, we report a fully automated adult mosquito release system operated from an uncrewed aerial vehi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 43 publications
2
63
2
Order By: Relevance
“…The results presented here support this finding. Bouyer et al [41] found decreased recapture when insects were released at 100 m compared to 50 m. The difference between Bouyer et al's [41] findings and those presented here may be because a smaller insect, with a lower terminal velocity, was released from a greater altitude and, consequently, may have experienced greater influence due to wind and/or drifting outside the study area.…”
Section: Describing the Pattern Of Recaptured Mothscontrasting
confidence: 61%
See 2 more Smart Citations
“…The results presented here support this finding. Bouyer et al [41] found decreased recapture when insects were released at 100 m compared to 50 m. The difference between Bouyer et al's [41] findings and those presented here may be because a smaller insect, with a lower terminal velocity, was released from a greater altitude and, consequently, may have experienced greater influence due to wind and/or drifting outside the study area.…”
Section: Describing the Pattern Of Recaptured Mothscontrasting
confidence: 61%
“…This study is not the first comparison of aerial and moving ground release methods, but it contributes to our understanding of aerial and moving ground release for sterile, adult Lepidoptera. Other studies have described aerial release methods [23,32,[39][40][41][42][43] and ground release methods [18,44] and have compared the releases of different life stages concurrently with different release methods [45,46]. Static ground release, moving ground release, and aerial release have all been examined to release sterile adult codling moths in BC, Canada [28,31,47], though moving ground release has been the method employed by the OKSIR program since 1994 [8].…”
Section: Comparing Release Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and b) the linkage of the phenotypic marker to the sex-determining genetic locus [28]. There is a renewed interest in revival and application of SIT for mosquitos [24,[29][30][31], as evidenced also by recent advances in refinement of irradiation doses and drone-mediated releases in the field as well as the recently published guidance framework and phased conditional approach for testing the SIT against Aedes mosquitoes [32][33][34]. Such strategies will be greatly facilitated by the availability of GSS developed through classical genetics, since there is documented efficiency through time and wide public acceptance [35].…”
Section: Introductionmentioning
confidence: 99%
“…Successful implementation of such projects relies on ensuring high levels of mosquito production and repeated releases of sterile males in overflooding numbers [25] that outcompete their wild counterparts within the target area [11,19]. To meet these requirements, novel methods and equipment including automatization of processes for the mass-rearing, sex separation, and release of mosquitoes are under development for deployment in the field [26]. Optimization of the mass-rearing conditions to produce eggs requires continuous efforts to achieve economic efficiency and high production rates.…”
Section: Introductionmentioning
confidence: 99%